Strategi manajemen perpustakaan dalam optimalisasi layanan informasi bagi pengguna - Pamungkas, Ratna (Jurnal Madako Education, 2025)
Management is a unique process that requires planning, organising, implementing, and monitoring. Management theories and principles guide effective library management. Development is a type of library management, and one area of ​​management that needs to be developed is service. The purpose of a library is not only to collect and organise all types of books and library materials, but also to utilise these resources to meet users' information needs optimally. This means that users must have access to data, collections, and various available knowledge materials. This concept is the core of library services. In the era of information technology development, libraries are required not only to provide traditional services but also to expand services such as internet services, information retrieval, digital services, library material selection, user education, administrative management, and cross-services. This study aims to determine how library management can improve service quality by managing relevant resources, technology, and service strategies. The research method is a literature review that analyses various scientific references on library management and service development. The results of the study indicate that effective library management requires applying modern management principles, improving librarian competency, and utilising digital technology to deliver faster, more efficient, and more user-friendly services.